2014
DOI: 10.3402/ejpt.v5.23950
|View full text |Cite
|
Sign up to set email alerts
|

The Australian Defence Force Mental Health Prevalence and Wellbeing Study: design and methods

Abstract: BackgroundThe Australian Defence Force (ADF) Mental Health Prevalence and Wellbeing Study (MHPWS) is the first study of mental disorder prevalence in an entire military population.ObjectiveThe MHPWS aims to establish mental disorder prevalence, refine current ADF mental health screening methods, and identify specific occupational factors that influence mental health. This paper describes the design, sampling strategies, and methodology used in this study.MethodAt Phase 1, approximately half of all regular Navy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 40 publications
(60 reference statements)
0
76
0
Order By: Relevance
“…The 2010 ADF Mental Health Prevalence and Wellbeing Study (MHPWS) employed a two‐phase design to estimate the prevalence of mental disorders, per criteria in the 10th revision of the International Classification of Diseases ( ICD‐10 ), across all currently serving regular ADF personnel (Van Hooff et al., ). This two‐phase design is well accepted in the investigation of mental disorder prevalence (Dunn, Pickles, Tansella, & Vazquez‐Barquero, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2010 ADF Mental Health Prevalence and Wellbeing Study (MHPWS) employed a two‐phase design to estimate the prevalence of mental disorders, per criteria in the 10th revision of the International Classification of Diseases ( ICD‐10 ), across all currently serving regular ADF personnel (Van Hooff et al., ). This two‐phase design is well accepted in the investigation of mental disorder prevalence (Dunn, Pickles, Tansella, & Vazquez‐Barquero, ).…”
Section: Methodsmentioning
confidence: 99%
“…For the ADF sample, detailed descriptions of stratification procedures and weighting are available elsewhere (Hodson, McFarlane, Van Hooff, & Davies, ; Van Hooff et al., ). In brief, mental disorder prevalence estimates were derived using a robust two‐stage weighting process, which attenuated the impact of low response rates as well as any selection and responder bias.…”
Section: Methodsmentioning
confidence: 99%
“…A significant amount of these methods require that the individual completes a questionnaire. In relation to military and seafaring populations, questionnaires include: the Primary care evaluation of mental disorders patient health questionnaire (PHQ) [214, 245, 246], the Kessler psychological distress scale [247, 248], the post-traumatic stress disorder checklist-civilian version (PLC-C) [213, 248250] and the General Health Questionnaire (GHQ-12) [213, 229, 251, 252]. …”
Section: Psychological Impactmentioning
confidence: 99%
“…Research found that the GHQ-12, which is the twelve item version, is just as reliable and valid as the longer version and takes less time to complete [255]. This questionnaire has been used in several military [213, 248, 252] and in particular naval service populations [229, 256], which indicates its value for providing knowledge about these populations.…”
Section: Psychological Impactmentioning
confidence: 99%
See 1 more Smart Citation